2014
DOI: 10.1071/an13268
|View full text |Cite
|
Sign up to set email alerts
|

Embryo production and gene expression in superovulated goats supplemented with de-oiled castor cake before and after detoxification treatment

Abstract: The use of alternative protein sources that do not impair animal performance is a feasible option to reduce costs associated with animal supplementation. Previous studies indicate that castor cake has a high protein value and good ruminal degradability, making it an attractive alternative dietary source for ruminants. Thus, the aim of this study was to evaluate the effects from ingestion of castor cake (treatment CC) or detoxified castor cake (treatment DCC) on serum IgG levels, in vivo production of goat embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…The peak antibody titres against B. abortus were on 7th day PS and later decreased. The IgG levels lowered and expressing of mRNA for HSP 70.1 decreased in goats fed either treated or detoxified CSC (Arruda et al, 2013) corroborating with present findings. Naidu et al (1988) observed formation of antitoxins against ricin in rams fed 30% CSC containing concentrate mixture along with mixed grass hay.…”
Section: Resultssupporting
confidence: 91%
“…The peak antibody titres against B. abortus were on 7th day PS and later decreased. The IgG levels lowered and expressing of mRNA for HSP 70.1 decreased in goats fed either treated or detoxified CSC (Arruda et al, 2013) corroborating with present findings. Naidu et al (1988) observed formation of antitoxins against ricin in rams fed 30% CSC containing concentrate mixture along with mixed grass hay.…”
Section: Resultssupporting
confidence: 91%